Sosialisasi Pengelolaan Sampah Berbasis Komunitas Menuju Lingkungan Bersih dan Sehat - Muh. Ma’ruf Idris; Nurlaely Nurlaely; Sahidah Sahidah; M.Syafruddin; Chaerunnisa Rumianti; Nur Syamsu; M. Rusli Djunaid (Lembaga Pengembangan Kinerja Dosen, 2026)
Household waste management remains a major challenge in rural areas, including Sunggumanai Village, Pattallassang District, Gowa Regency. Low public awareness and the absence of a structured community-based waste management system have negatively affected environmental quality and public health. This community service activity aimed to enhance community knowledge, awareness, and participation through the socialization of community-based waste management toward a clean and healthy environment. The activity was conducted on September 27, 2025, involving 30 participants consisting of community representatives, housewives, youth, and community leaders. The methods applied included educational socialization, participatory discussions, and waste segregation simulations based on the 3R principles (Reduce, Reuse, Recycle). The results indicated an improvement in participants’ understanding of waste types, the environmental and health impacts of improper waste management, and the importance of collective waste management practices. Participants also demonstrated positive attitudes and readiness to implement household waste segregation, as well as emerging ideas for establishing community-based waste management initiatives. In conclusion, this activity proved to be an effective initial step in promoting behavioral change toward sustainable waste management and supporting the creation of a clean and healthy village environment.